Increase Understanding Of Gratitude With Video-Based Learning At Madrasah Tsanawiyah - Ismail, Taufik (Jurnal Multidisiplin Indonesia, 2024)
This research aims to assess the efficacy of video-based learning in clarifying the concept of gratitude for students attending Madrasah Tsanawiyah. This research employed a quantitative descriptive approach. The study utilized a sample size of twenty-eight students. Participants in this research endeavor were required to reply to inquiries posed by the investigators both before and after seeing the film. A substantial increase in the accuracy of responses was seen among participants after seeing the video provided by the researcher. The video piques the curiosity of the responders, who also demonstrate comprehension of the intended video material. Students benefit from the use of video in instruction and learning because it piques their attention and compels them to acquire valuable knowledge. Across the board, video-based learning may be integrated into the instructional and learning processes. Lessons that are presented visually are more uncomplicated to retain and comprehend. Using video helps pique pupils' curiosity about acquiring new knowledge.Using video helps pique pupils’ curiosity about acquiring new knowledge.